Effect of 12-week endurance training on biochemical parameters in elite football players: A comprehensive analysis - Farooque, Sm; Mitra, Mukesh; Das , Prasanta Kumar (UIR Press, 2023)
Endurance training plays a pivotal role in football performance, shaping players’ cardiovascular fitness and metabolic adjustments. The purpose of this study is to investigate the different changes in biochemical parameters after exposure to 12 weeks of circuit training based on endurance in football. A total of fifteen elite football players, with an average age of 16.87 ± 1.13 years, an average weight of 61.87 ± 5.94 kg, and an average height of 172.82 ± 5.18 cm, participated in the study. On average, they had been training for 5.0 ± 1.0 years and had intermediate experience in national-level competitions for 4.0 ± 1.0 years. Following the initial data collection, the participants engaged in a twelve-week endurance training programme, involving one hour of daily training for four days a week. Pre-experimental designs were used in the data collection process. Further, for the analysis and extraction of data, descriptive statistics and t-tests were employed. The significance level was set at P < 0.05. Significant changes were found from baseline to post-treatment in each player’s biochemical parameters. A significant increase in HDL, haemoglobin, creatine, and RBC and a significant decrease in LDL and VLDL were observed. The findings of this study underscore the potential benefits of endurance training for elite football players, as reflected in positive alterations in various biochemical parameters. However, for more comprehensive conclusions and a deeper understanding of the broader implications. Future research is recommended with larger sample sizes, control groups, and more detailed performance outcome measurements. This research contributes to our knowledge of the physiological responses of elite football players to endurance training and the potential advantages, it offers in optimising their performance and overall health.